Graffiti Virtual Exhibition “Pandemic Youth” - Donna Carollina (Graduate School of Institut Seni Indonesia Yogyakarta, 2020)
In the middle of March 2020, Indonesia declared a Covid-19 emergency. This pandemic has an impact on art activities, including the artistic world of graffiti. During this time, the activities of graffiti artists in public spaces were increasingly limited. However, this limitation does not dampen their spirit, especially in terms of organizing exhibitions. Where on May 17, 2020, they held a virtual exhibition titled